Teachers’ Conceptions of Teaching Chinese Descriptive Composition With Interactive Spherical Video-Based Virtual Reality - Chen, Mengyuan; Chai, Ching-Sing; Jong, Morris Siu-Yung; Jiang, Michael Yi-Chao (Frontiers in Psychology, 2021)
This paper reports teachers' conceptions of teaching with regards to the use of interactive spherical video-based virtual reality (ISV-VR) in Chinese descriptive composition writing. Twenty-one secondary teachers in Hong Kong involved in an ISV-VR-supported Chinese descriptive writing program participated in this phenomenograhic study. Analyses of the semi-structured interviews establish seven conception categories: (1) offering students more observational opportunities; (2) improving students' writing skills; (3) promoting students' learning participation and motivation; (4) shifting learning from teacher-centric to student-centric, (5) enhancing collaborative learning among students; (6) cultivating students' positive values and moral character, and (7) shaping students' self-identity as "writers". These categories form a hierarchy from skill-oriented to community-oriented, and finally to identity-oriented conception. The impact of this study on the first language (L1) writing education and teachers' conceptions development is discussed in this study. The findings may provide researchers and practitioners with novel insight into the teaching of composition writing in the contexts of L1 acquisition supported by virtual reality technology.